Bad altitude: Categorizing elevation produces spurious association with concussions in the National Football League (NFL) - Binney, Z. O.; Smoliga, J. M. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
OBJECTIVE: To assess whether prior analyses, where there was a relationship between altitude and concussion rates in American football, would replicate using a larger data set and altitude as a continuous variable.